MRI interactions of a fully implantable pressure monitoring device. Issue 5 (10th April 2015) - Stehlin, Ellyce F.; McCormick, Daniel; Malpas, Simon C.; Pontré, Beau P.; Heppner, Peter A.; Budgett, David M.
<x xml:space="preserve">Abstract</x> Purpose To investigate the potential patient risk and interactions between a prototype implantable pressure monitoring device and a 3T clinical magnetic resonance imaging (MRI) machine to guide device design towards MR Conditional safety approval. Materials and Methods The pressure monitor device contained a catheter‐mounted piezo‐resistive pressure sensor, rechargeable battery, wireless communication system, and inductive pickup coil. Standard testing methods were used to guide experiments to investigate static field induced force and torque, radiofrequency (RF)‐induced heating, image artifacts, and the MR's effect on device function. The specific clinical application of intracranial pressure monitoring was considered. RF‐induced heating experiments were supported by numerical modeling of the RF body coil, the device, and experimental phantom. Results Sensing catheter lead length and configuration was an important component of the device design. A short 150 mm length catheter produced a heating effect of less than 2°C and a long 420 mm length catheter caused heating of 7.2°C. Static magnetic field interactions were below standard safety risk levels and the MR did not interfere with device function; however, artifacts have the potential to interfere with image quality. Conclusion Investigation of MR interactions at the prototype stage provides useful implantable device design guidance and confidence that an implantable pressure monitor may be able to achieve MR Conditional safety approval. J. Magn. Reson. Imaging 2015;42:1441–1449.